Methodology of justification of tactical and technical requirements for movable means of repairing arms and military equipment - Dachkovskyi, Volodymyr (Social Development and Security, 2019)
An analysis of the qualitative and quantitative state of mobile repair equipment, which are armed with repair units (military units), shows that the existing park consists mainly of samples that were designed in the 70’s. The main disadvantage of these is the physical and moral aging and the lack of compliance with the requirements for weapons renewal systems and military equipment. Accordingly, there are drawbacks and inconsistencies between the need for repair work and the production capabilities of rolling stock. Therefore, the article proposes a technique for substantiating the tactical and technical requirements for mobile weapons repair and military equipment operating at different levels of the hierarchy. All indicators considered in this methodology have their own specifics in the development of different types of equipment. However, they can be expressed by such groups of requirements as tactical, technical, operational, production and economic. The application of this technique will provide an opportunity to obtain technical outlines of mobile repair equipment for battalion, brigade, operational, strategic levels. As base platforms for mobile repair tools, it is proposed to create base platforms built on a modular basis. These base platforms must allow for the placement of the control module, the power unit, the transmission module, the chassis module, in addition, the platform base must contain cells for mounting those modules to allow for the rapid replacement of damaged modules, the possibility of mounting container modules with process equipment. For placement of technological equipment it is proposed to use bodies built on a modular principle. Assembly of such bodies with modules of technological equipment and their subsequent use will be possible depending on the intended purpose of the movable means of repair. In this case it will be possible to largely solve the problem of standardization and specialization of equipment.